2021
DOI: 10.1071/bt20116
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire recruitment and resprouting of a threatened montane eucalypt

Abstract: Changing climate is predicted to result in increased frequency and size of wildfires in south-eastern Australia. With increasing area burnt there is increased potential for entire species distributions to be burnt in a single fire event. This is particularly the case for range-restricted threatened species. Eucalyptus canobolensis (L.A.S.Johnson & K.D.Hill) J.T.Hunter is restricted to Mount Canobolas, New South Wales, Australia. In 2018, the majority of the E. canobolensis population was burnt by wildf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Fire severity is projected to further increase under climate change in eastern Australia, posing a significant threat to the recovery of fire-sensitive native plant species (Williams et al 2009;Nolan et al 2021;van Oldenborgh et al 2021). Importantly, threatened species that are reliant on seedling establishment post-fire for persistence may be significantly impacted by changes to this aspect of fire regime (Bowman et al 2014;Zimmer et al 2021). In this study, we observed no apparent relationship among fire severity and post-fire seedling recruitment and growth in our study species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire severity is projected to further increase under climate change in eastern Australia, posing a significant threat to the recovery of fire-sensitive native plant species (Williams et al 2009;Nolan et al 2021;van Oldenborgh et al 2021). Importantly, threatened species that are reliant on seedling establishment post-fire for persistence may be significantly impacted by changes to this aspect of fire regime (Bowman et al 2014;Zimmer et al 2021). In this study, we observed no apparent relationship among fire severity and post-fire seedling recruitment and growth in our study species.…”
Section: Discussionmentioning
confidence: 99%
“…2014; Zimmer et al . 2021). In this study, we observed no apparent relationship among fire severity and post‐fire seedling recruitment and growth in our study species.…”
Section: Discussionmentioning
confidence: 99%